A nickel-based double metal hydroxide / magnesium hydroxide composite powder and its preparation method and application

Through the design and preparation method of nickel-based layered bimetallic hydroxide/magnesium hydroxide composite powder, the problems of low flame retardant efficiency and high filling amount are solved, and the goal of obtaining excellent flame retardant effect at low filling amount is achieved, and the comprehensive performance of the composite material is improved.

CN115975259BActive Publication Date: 2025-03-18JIANGXI GUANGYUAN CHEM +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211539432.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-03-18
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

As a flame retardant, magnesium hydroxide has low flame retardant efficiency and requires a higher fill amount to obtain a better flame retardant effect. High fill amount will affect the comprehensive performance of the product, especially the mechanical properties, limiting its application in a wider field.

Method used

The nickel-based layered bimetallic hydroxide/magnesium hydroxide composite powder is used to coat the magnesium hydroxide core through the nickel-based layered double hydroxide shell to form a core-shell structure, which improves the thermal stability and flame retardant properties of the composite powder, and optimizes the structure and performance of the composite powder through heat treatment and hybridization reaction.

Benefits of technology

A small amount of filling in the polymer matrix can achieve excellent flame retardant effect, significantly improve the flame retardant and smoke suppression performance of the composite powder, avoid the impact on the mechanical properties of the composite material, and the process is simple and easy to operate, suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115975259B_ABST
    Figure CN115975259B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of functional materials, and provides a nickel-based layered double hydroxide / magnesium hydroxide composite powder, and a preparation method and application thereof. The present invention uses a nickel-based layered double hydroxide as an outer shell to coat magnesium hydroxide, which can give full play to the catalytic carbonization characteristics of the nickel-based double hydroxide and the smoke suppression characteristics of magnesium hydroxide. The two produce a certain synergistic ability, effectively improving the flame retardant and smoke suppression and other comprehensive properties of the composite powder; and after the nickel-based layered double hydroxide is coated, the oil absorption of the magnesium hydroxide powder can be significantly reduced, and its dispersibility in the composite material can be improved, thereby reducing the filling amount in the composite material. The nickel-based layered double hydroxide / magnesium hydroxide composite powder of the present invention is added to a polymer matrix such as PVC, and the resulting composite material has excellent flame retardant properties and good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and in particular to a nickel-based layered double metal hydroxide / magnesium hydroxide composite powder and a preparation method and application thereof. Background Art

[0002] From the perspective of the nature of polymer combustion, flame retardant technology, as a passive protection technology, refers to the use of some functional materials to cut off the combustion cycle, so that it can improve the application safety of polymer-based materials. With the popularization of environmental protection concepts in recent years and the guidance of relevant policies, flame retardant functional materials are developing in the direction of halogen-free, phosphide-free, and smoke suppression. Among them, magnesium hydroxide (MH), as a typical metal hydroxide, has been widely used for its non-toxic, no secondary pollution, excellent thermal stability, and clean and environmentally friendly flame retardant process. At present, magnesium hydroxide is mainly produced by chemical synthesis and mechanical methods. The mechanical method is generally favored by the market because of its relatively green and environmentally friendly preparation process, low energy consumption and low cost.

[0003] Magnesium hydroxide is considered to be one of the most promising environmentally friendly inorganic smoke suppressant flame retardants. This effect has been confirmed by some research results. For example, the Chinese invention patent CN201911016755.X uses a hydrothermal method to prepare large-particle magnesium hydroxide flame retardant, the Chinese invention patent CN201611014049.8 uses a composite precipitant to prepare magnesium hydroxide flame retardant, and the Chinese invention patent CN201810468588.1 uses surfactants to improve the lipophilicity and dispersibility of magnesium hydroxide, thereby further improving its flame retardant properties.

[0004] Metal hydroxides represented by magnesium hydroxide are mostly used in wire and cable insulation sheaths, as well as some soft products such as rubber and resin. However, one of the important problems they face is that their flame retardant efficiency is relatively low, and a higher filling amount (usually >50wt%) is required to obtain a better flame retardant effect. A higher filling amount will greatly affect the comprehensive properties of the product (especially the mechanical properties), which seriously restricts its further application in a wider range of fields. In view of the above defects, some researchers have tried to carry out necessary hybridization (compounding) modification on magnesium hydroxide. For example: Chinese invention patent CN201810588210.5 discloses a method for preparing a magnesium hydroxide-zinc borate composite flame retardant, wherein zinc hydroxide is added to an ammonium chloride solution of magnesium hydroxide, and a coagulant is added to obtain a magnesium hydroxide-zinc borate composite flame retardant. Although this method can improve the composite uniformity and stability of the flame retardant to a certain extent, it is necessary to add a large amount of water-soluble coagulant to protect the zinc borate with poor temperature resistance, which increases the preparation cost to a certain extent; another defect is that the composite flame retardant prepared using a water-soluble coagulant is easy to absorb moisture during storage, and even loses its original spatial structure, resulting in the failure of the flame retardant effect, which has a great impact on subsequent applications. For example: Chinese invention patent CN201810619191.8 discloses a method for preparing a basic magnesium borate / magnesium hydroxide composite flame retardant, which is specifically obtained by adding alkali solution precipitation, high shear dispersion, hydrothermal reaction, and solid-liquid separation. Although this method can obtain a homogeneous co-precipitated composite flame retardant, its preparation process requires multiple steps of reaction, which is relatively complicated, and corrosive liquids such as alkali solution are required in the preparation process, which is dangerous. At the same time, it is also necessary to use a hydrothermal method to prepare a composite flame retardant precursor slurry, which has high process requirements and high costs, and is not conducive to promotion and application.

[0005] Although the above methods can improve some defects of MH to a certain extent, it is still difficult to improve the comprehensive performance of MH. In actual use, a large amount of modified MH still needs to be added, which is difficult to meet the needs of further universalization of MH. Summary of the invention

[0006] In view of this, the present invention provides a nickel-based layered double metal hydroxide / magnesium hydroxide composite powder and a preparation method and application thereof. The nickel-based layered double metal hydroxide / magnesium hydroxide composite powder provided by the present invention has high thermal stability and flame retardancy, and has good barrier effect and catalytic carbonization effect, and a small amount of filling in a polymer matrix can achieve excellent flame retardant effect.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A nickel-based layered double hydroxide / magnesium hydroxide composite powder comprises a nickel-based layered double hydroxide shell and a magnesium hydroxide core; the molar ratio of the magnesium hydroxide core to the nickel-based layered double hydroxide shell is 1:(0.5-10).

[0009] Preferably, the particle size of the magnesium hydroxide core is 0.9 to 1.6 μm.

[0010] Preferably, the nickel-based layered double hydroxide is one of nickel aluminum layered double hydroxide, nickel cobalt layered double hydroxide, nickel iron layered double hydroxide, nickel manganese layered double hydroxide, nickel gallium layered double hydroxide, nickel rhodium layered double hydroxide, nickel zinc layered double hydroxide, nickel copper layered double hydroxide, nickel lead layered double hydroxide, nickel cadmium layered double hydroxide, nickel chromium layered double hydroxide, nickel calcium layered double hydroxide and nickel vanadium layered double hydroxide.

[0011] Preferably, the particle size of the nickel-based double hydroxide / magnesium hydroxide composite powder is 1.0 to 2.0 μm.

[0012] The present invention also provides a method for preparing the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder described in the above scheme, comprising the following steps:

[0013] Heat-treating the nickel-based layered double metal hydroxide in an inert atmosphere and then cooling the layered double metal hydroxide to obtain a heat-treated nickel-based layered double metal hydroxide;

[0014] The heat-treated nickel-based layered double metal hydroxide is mixed with a magnesium hydroxide dispersion to carry out a hybridization reaction to obtain a nickel-based layered double metal hydroxide / magnesium hydroxide composite powder.

[0015] Preferably, the heat treatment temperature is 100-400° C., and the heat treatment time is 0.5-48 h.

[0016] Preferably, the hybridization reaction is carried out at a temperature of 60 to 145° C. for a time of 0.5 to 24 h, and the hybridization reaction is carried out under stirring conditions.

[0017] The present invention also provides the use of the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder described in the above scheme or the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder prepared by the preparation method described in the above scheme as a flame retardant.

[0018] The present invention also provides a halogen-free flame-retardant polyvinyl chloride composite material, comprising the following components in parts by weight: 50-60 parts of PVC, 2-6 parts of nickel-based layered double hydroxide / magnesium hydroxide composite powder, and 50-60 parts of an auxiliary agent; the nickel-based layered double hydroxide / magnesium hydroxide composite powder is the nickel-based layered double hydroxide / magnesium hydroxide composite powder described in the above scheme or the nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared by the preparation method described in the above scheme.

[0019] Preferably, the auxiliary agent includes one or more of a plasticizer, an anti-drip agent, a stabilizer, a reinforcing agent and a synergist.

[0020] The present invention provides a nickel-based layered double metal hydroxide / magnesium hydroxide composite powder, including a nickel-based layered double hydroxide shell and a magnesium hydroxide core. The present invention adopts nickel-based layered double metal hydroxide (nickel-based LDHs) as a shell to coat magnesium hydroxide (MH), and the nickel-based layered double metal hydroxide is full of a large number of metal ions with catalytic effects, which can play a role in catalytic carbonization during the combustion process, thereby improving the flame retardant effect of the composite powder; and the present invention adopts nickel-based layered double metal hydroxide to coat magnesium hydroxide, which can significantly reduce the oil absorption of magnesium hydroxide powder, improve the corresponding compatibility, thereby improving its dispersibility in composite materials, and then significantly improve the flame retardant and smoke suppression performance of the composite powder, so as to meet the flame retardant requirements under the condition of low filling amount, and avoid affecting the mechanical properties of the composite material; the composite powder provided by the present invention can give full play to the catalytic carbonization of nickel-based double metal hydroxide and the smoke suppression characteristics of magnesium hydroxide, and the two produce a certain synergistic ability, effectively improve the comprehensive performance of the composite powder such as flame retardant and smoke suppression, and has good dispersibility, small filling amount in composite materials, and has broad application prospects.

[0021] The present invention also provides a method for preparing the nickel-based layered double hydroxide / magnesium hydroxide composite powder described in the above scheme. The present invention first heat-treats the nickel-based double hydroxide, and then hybridizes it with magnesium hydroxide. The nickel-based double hydroxide after high-temperature treatment can remove water molecules and part of the anions of the nickel-based layered double hydroxide to form a double metal oxide with good structure, higher thermal stability and further homogenized active site distribution, thereby further improving the comprehensive performance of the nickel-based layered double hydroxide / magnesium hydroxide composite powder; in addition, the acid and alkali resistance of the nickel-based double hydroxide after high-temperature treatment is improved, which can further improve the acid and alkali resistance of the finally obtained composite powder, which is beneficial to its application in acidic or alkaline polymer matrices; the preparation method provided by the present invention is simple in process and easy to operate, and is suitable for large-scale industrial production.

[0022] The present invention also provides a halogen-free flame-retardant polyvinyl chloride composite material. When the nickel-based layered double hydroxide / magnesium hydroxide composite powder of the present invention is added to a PVC matrix, the catalytic carbonization of the nickel-based layered double hydroxide and the smoke suppression of the magnesium hydroxide can be fully utilized. The obtained composite material has excellent flame retardant performance, and the amount of the nickel-based layered double hydroxide / magnesium hydroxide composite powder added is small, which will not affect the mechanical properties of the composite material. In addition, since the nickel-based layered double hydroxide / magnesium hydroxide composite powder of the present invention is white or light yellow, it will not have an obvious dyeing effect on the PVC matrix, which helps to maintain the original color of the PVC matrix and meet the needs of subsequent dyeing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a high-magnification scanning electron microscope image of the nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared in this example;

[0024] Figure 2 : is the particle size distribution diagram of the nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared in this example. DETAILED DESCRIPTION

[0025] The invention provides a nickel-based layered double hydroxide / magnesium hydroxide composite powder, comprising a nickel-based layered double hydroxide shell and a magnesium hydroxide core; the molar ratio of the magnesium hydroxide core to the nickel-based layered double hydroxide shell is 1:(0.5-10).

[0026] In the present invention, the particle size of the magnesium hydroxide core is preferably 0.9-1.6 μm, more preferably 1-1.2 μm; the molar ratio of the magnesium hydroxide core to the nickel-based layered double hydroxide shell is 1:(0.5-10), preferably 1:(1-8), more preferably 1:(1-3).

[0027] In the present invention, the nickel-based layered double hydroxide is preferably one of nickel aluminum layered double hydroxide, nickel cobalt layered double hydroxide, nickel iron layered double hydroxide, nickel manganese layered double hydroxide, nickel gallium layered double hydroxide, nickel rhodium layered double hydroxide, nickel zinc layered double hydroxide, nickel copper layered double hydroxide, nickel lead layered double hydroxide, nickel cadmium layered double hydroxide, nickel chromium layered double hydroxide, nickel calcium layered double hydroxide and nickel vanadium layered double hydroxide.

[0028] In the present invention, the particle size of the nickel-based double hydroxide / magnesium hydroxide composite powder is preferably 1.0 to 2.0 μm.

[0029] The present invention also provides a method for preparing the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder described in the above scheme, comprising the following steps:

[0030] Heat-treating the nickel-based layered double metal hydroxide in an inert atmosphere and then cooling the layered double metal hydroxide to obtain a heat-treated nickel-based layered double metal hydroxide;

[0031] The heat-treated nickel-based layered double metal hydroxide is mixed with a magnesium hydroxide dispersion to carry out a hybridization reaction to obtain a nickel-based layered double metal hydroxide / magnesium hydroxide composite powder.

[0032] The present invention heat-treats the nickel-based layered double metal hydroxide in an inert atmosphere and then cools it to obtain the heat-treated nickel-based layered double metal hydroxide. In the present invention, the temperature of the heat treatment is preferably 100 to 400°C, more preferably 200 to 300°C, the time of the heat treatment is preferably 0.5 to 48 hours, more preferably 1 to 24 hours; the inert gas is preferably selected from one of helium, neon, argon, krypton, and xenon, more preferably argon; the type of the nickel-based layered double metal hydroxide is consistent with the above scheme, and will not be repeated here; the present invention has no special requirements for the cooling method, and it can be cooled naturally to room temperature.

[0033] After obtaining the nickel-based layered double metal hydroxide after heat treatment, the present invention mixes the nickel-based layered double metal hydroxide after heat treatment with a magnesium hydroxide dispersion for hybridization reaction to obtain a nickel-based layered double metal hydroxide / magnesium hydroxide composite powder. In the present invention, the solvent of the magnesium hydroxide dispersion is preferably one or more of ethanol, methanol, ethyl acetate, tetrahydrofuran, dioxane, N,N-dimethylformamide and acetonitrile, and the concentration of the magnesium hydroxide dispersion is preferably 0.1M to 100M; in the present invention, the magnesium hydroxide is preferably magnesium hydroxide prepared by a physical method or a chemical method, wherein the magnesium hydroxide prepared by a physical method has no lamellar structure, and the magnesium hydroxide prepared by a chemical method has a lamellar structure, and the particle size of the magnesium hydroxide is consistent with the above scheme, which will not be repeated here. The present invention has no special requirements for the preparation method of the magnesium hydroxide dispersion, and the magnesium hydroxide can be evenly dispersed in the solvent.

[0034] In the present invention, the molar ratio of the magnesium hydroxide and the nickel-based layered double hydroxide is consistent with the above-mentioned scheme, which will not be repeated here; when the molar ratio of the nickel-based layered double hydroxide to the magnesium hydroxide is less than 0.5:1, the nickel-based layered double hydroxide on the surface cannot be completely covered on the magnesium hydroxide powder; when the molar ratio of the nickel-based layered double hydroxide to the magnesium hydroxide is greater than 10:1, the agglomeration of the nickel-based layered double hydroxide will occur, resulting in limited coverage effect on the surface of the magnesium hydroxide.

[0035] In the present invention, the temperature of the hybridization reaction is preferably 60-145°C, more preferably 80-120°C. In a specific embodiment of the present invention, the hybridization reaction is preferably carried out under reflux conditions; the time of the hybridization reaction is preferably 0.5-24h, more preferably 2-12h. The hybridization reaction is preferably carried out under stirring conditions, and the stirring is preferably mechanical stirring, and the stirring rate is preferably 100-900rpm. During the hybridization reaction, the nickel-based layered double hydroxide can form hydrogen bonds with the hydroxyl groups on the surface of MH because of the separation of the layers and the large number of hydroxyl groups in the structure, and then adhere to the surface of MH to form a composite powder with a core-shell structure.

[0036] After the hybridization reaction is completed, the present invention preferably sequentially washes, centrifuges and freeze-dries the obtained product; the washing detergent is preferably one or more of ethanol, methanol, tetrahydrofuran, ethyl acetate, acetonitrile and deionized water; the number of washings is preferably 2 to 3 times; the speed of the centrifugation is preferably 1000 to 9000 rpm, and the time of the centrifugation is preferably 10 to 60 minutes; the freeze-drying is preferably: the solid powder obtained by centrifugation is dispersed in a small amount of deionized water and frozen, and vacuum sublimated at low temperature to obtain a nickel-based layered double hydroxide / magnesium hydroxide composite powder; the freeze-drying temperature is preferably -50 to -10°C, and the freeze-drying time is preferably 1 to 48 hours. The nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared by the present invention is white or light yellow powder.

[0037] The present invention also provides the use of the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder described in the above scheme or the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder prepared by the preparation method described in the above scheme as a flame retardant. The nickel-based layered double metal hydroxide / magnesium hydroxide composite powder provided by the present invention has high thermal stability, good flame retardant and smoke suppression properties, good barrier effect and catalytic carbonization effect, and is suitable for polymer matrices with large smoke emission. In a specific embodiment of the present invention, the polymer matrix is ​​preferably PVC, ABS, PS or PET, and the amount of the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder is preferably 1% to 15% of the weight of the polymer matrix, and more preferably 2% to 6%.

[0038] The present invention also provides a halogen-free flame-retardant polyvinyl chloride composite material, comprising the following components in parts by weight: 50-60 parts of PVC, 2-6 parts of nickel-based layered double metal hydroxide / magnesium hydroxide composite powder, and 50-60 parts of an auxiliary agent.

[0039] The halogen-free flame-retardant polyvinyl chloride composite material provided by the present invention comprises 50 to 60 parts of PVC, preferably 55 to 58 parts. In the present invention, the PVC is used to produce soft films, sheets, pipes, cables, profiles, etc. Specifically, the melt index of the PVC is preferably 750 g / 10min to 1300 g / 10min, the melting temperature is preferably 150 to 180°C, and the average degree of polymerization is preferably 900 to 1800; in a specific embodiment of the present invention, the brand of the PVC is preferably one of S-700, S-1000, SG-3, SG-5, SLP-1000, SLK-1000, SR-800, WS-800S, WS-1000S, WS-1300S and P-1000.

[0040] Based on the weight proportion of the PVC, the halogen-free flame-retardant polyvinyl chloride composite material provided by the present invention comprises 2 to 6 parts, preferably 3 to 4 parts, of a nickel-based layered double hydroxide / magnesium hydroxide composite powder; the nickel-based layered double hydroxide / magnesium hydroxide composite powder is the nickel-based layered double hydroxide / magnesium hydroxide composite powder described in the above scheme or the nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared by the preparation method described in the above scheme, which will not be described in detail here.

[0041] Based on the weight of the PVC, the halogen-free flame-retardant polyvinyl chloride composite material provided by the present invention includes 50 to 60 parts of additives, preferably 52 to 55 parts. In the present invention, the additives preferably include one or more of plasticizers, anti-drip agents, stabilizers, reinforcing agents and synergists.

[0042] In the present invention, the plasticizer is preferably a dialkyl phthalate, and the dialkyl phthalate is preferably one or more of dioctyl phthalate, dimethyl phthalate, dipentyl phthalate, dipropyl phthalate, dihexyl phthalate, dibutyl phthalate, dinonyl phthalate, diisobutyl phthalate, dihexyl phthalate, dicyclohexyl phthalate and octyl decyl phthalate, more preferably dioctyl phthalate.

[0043] In the present invention, the anti-dripping agent is preferably one or more of polytetrafluoroethylene, polyhexafluoroethylene and poly(tetrafluoroethylene-hexafluoroethylene), and the density of the anti-dripping agent is preferably 2.1-2.2 g / cm 3 .

[0044] In the present invention, the stabilizer is preferably one or more of a calcium zinc stabilizer, a composite heat stabilizer and an organic tin stabilizer, and more preferably a barium cadmium zinc stabilizer; the composite heat stabilizer is mainly a calcium zinc composite stabilizer, which is composited with a calcium salt, a zinc salt, a lubricant, an antioxidant, etc. The present invention has no special requirements on the source of the composite heat stabilizer, and a commercially available composite heat stabilizer can be used.

[0045] In the present invention, the reinforcing agent is preferably calcium carbonate powder, and the synergist is preferably antimony trioxide. The reinforcing agent and the synergist are beneficial to the processing process and also have a certain effect on improving the mechanical properties of the composite material.

[0046] In a specific embodiment of the present invention, the weight proportion of the plasticizer is preferably 1 to 10 parts, the weight proportion of the anti-dripping agent is preferably 1 to 3 parts, the weight proportion of the stabilizer is preferably 1 to 55 parts, the weight proportion of the reinforcing agent is preferably 1 to 32 parts, and the weight proportion of the synergist is preferably 1 to 10 parts.

[0047] In the present invention, the preparation method of the halogen-free flame-retardant polyvinyl chloride composite material preferably comprises the following steps:

[0048] PVC, nickel-based layered double hydroxide / magnesium hydroxide composite powder and additives are mixed and then kneaded to obtain a halogen-free flame-retardant polyvinyl chloride composite material.

[0049] In the present invention, the mixing is preferably carried out in a high-speed mixer, and the mixing rotation speed is preferably 60 to 500 rpm, more preferably 100 rpm; the kneading is preferably carried out in a double-roll open mill, and the kneading temperature is preferably 150 to 180°C, more preferably 170°C, and the kneading time is preferably 6 to 15 min, more preferably 9 min.

[0050] The following will combine the embodiments of the present invention to clearly and completely describe the technical solution of the present invention.

[0051] Example 1

[0052] Preparation of nickel-based layered double hydroxide / magnesium hydroxide composite powder:

[0053] (1) placing a nickel-cobalt layered double hydroxide in an argon gas atmosphere, heating it at 250° C. for 3 h, and then cooling it to room temperature to obtain a heat-treated nickel-based layered double hydroxide;

[0054] (2) 1.0 mol of MH (physical method) with a particle size of 1.0 μm was uniformly dispersed in ethanol to obtain an MH dispersion; 1.0 mol of the aforementioned heat-treated nickel-based layered double hydroxide was added to the MH dispersion, mechanically stirred at 78° C. and refluxed at a speed of 500 rpm for 12 h, and the reaction mixture was allowed to react.

[0055] After completion, the mixture was washed repeatedly with deionized water for 2 to 3 times, centrifuged at 5000 rpm for 20 min, and freeze-dried at -40°C for 24 h to obtain a nickel-based layered double hydroxide / magnesium hydroxide composite powder.

[0056] The obtained nickel-based layered double hydroxide / magnesium hydroxide composite powder is used to prepare halogen-free flame-retardant PVC. The preparation method is as follows: 50 parts of PVC (model WS-1000S) with a melt index of 1000g / 10min, 4 parts of nickel-based layered double hydroxide / magnesium hydroxide composite powder, 20 parts of dioctyl phthalate, 32 parts of calcium carbonate, 2 parts of barium cadmium zinc stabilizer, 1 part of polytetrafluoroethylene, and 1 part of antimony trioxide are uniformly mixed in a high-speed mixer, and then mixed by a double-roll mill at a mixing speed of 100rpm to obtain a halogen-free flame-retardant PVC composite material; wherein the temperature of the double-roll mill is set to 170°C and the mixing time is 9min.

[0057] Figure 1 This is a high-power scanning electron microscope image of the nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared in this example. Figure 1 It can be seen that there is a layer of coating on the surface of MH, which is relatively rough and wrinkled, and the surface coating is relatively uniform, indicating that the nickel-based double hydroxide wraps the magnesium hydroxide relatively well.

[0058] Figure 2 : is the particle size distribution diagram of the nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared in this example; Figure 2 It can be seen that the number average particle size distribution of the nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared in Example 1 is mainly concentrated around 1.2 μm, and the distribution is relatively uniform.

[0059] Example 2

[0060] (1) placing a nickel-aluminum layered double hydroxide in an argon gas atmosphere, heating it at 100° C. for 48 hours, and then cooling it to room temperature to obtain a heat-treated nickel-based layered double hydroxide;

[0061] (2) 1.0 mol of MH (physical method) with a particle size of 1.0 μm was uniformly dispersed in methanol to obtain an MH dispersion; 0.5 mol of the aforementioned heat-treated nickel-based layered double hydroxide was added to the MH dispersion, mechanically stirred at 100 rpm and refluxed for 24 h at 60° C. After the reaction was completed, the mixture was repeatedly washed with deionized water for 2 to 3 times, centrifuged at 1000 rpm for 60 min, and freeze-dried at -10° C. for 48 h to obtain a nickel-based layered double hydroxide / magnesium hydroxide composite powder.

[0062] The obtained nickel-based layered double hydroxide / magnesium hydroxide composite powder is used to prepare halogen-free flame-retardant PVC. The preparation method is as follows: 55 parts of PVC (model S-700) with a melt index of 750g / 10min, 4 parts of nickel-based layered double hydroxide / magnesium hydroxide, 20 parts of dioctyl phthalate, 32 parts of calcium carbonate, 2 parts of barium cadmium zinc stabilizer, 1 part of polytetrafluoroethylene, and 1 part of antimony trioxide are uniformly mixed in a high-speed mixer, and then mixed by a double-roll mill at a mixing speed of 100rpm to obtain a halogen-free flame-retardant PVC composite material; wherein the temperature of the double-roll mill is set to 170°C and the mixing time is 9min.

[0063] Example 3

[0064] (1) placing a nickel-iron layered double hydroxide in an argon gas atmosphere, heating it at 400° C. for 0.5 h, and then cooling it to room temperature to obtain a heat-treated nickel-based layered double hydroxide;

[0065] (2) 1.0 mol of MH (physical method) with a particle size of 1.0 μm was uniformly dispersed in N'N-dimethylformamide to obtain an MH dispersion; 10.0 mol of the above-mentioned heat-treated nickel-based layered double hydroxide was added to the above-mentioned MH dispersion, and mechanically stirred at 900 rpm and refluxed for 0.5 h at 145° C. After the reaction was completed, it was repeatedly washed with deionized water for 2 to 3 times, centrifuged at 9000 rpm for 10 min, and freeze-dried at -50° C. for 1 h to obtain a nickel-based layered double hydroxide / magnesium hydroxide composite powder.

[0066] The obtained nickel-based layered double hydroxide / magnesium hydroxide composite powder is used to prepare halogen-free flame-retardant PVC. The preparation method is as follows: 60 parts of PVC (model SG-3) with a melt index of 1300g / 10min, 4 parts of nickel-based layered double hydroxide / magnesium hydroxide, 20 parts of dioctyl phthalate, 32 parts of calcium carbonate, 2 parts of barium cadmium zinc stabilizer, 1 part of polytetrafluoroethylene, and 1 part of antimony trioxide are uniformly mixed in a high-speed mixer, and then mixed by a double-roll mill at a mixing speed of 100rpm to obtain a halogen-free flame-retardant PVC composite material; wherein the temperature of the double-roll mill is set to 170°C and the mixing time is 9min.

[0067] Example 4

[0068] (1) placing a nickel-gallium layered double hydroxide in an argon gas atmosphere, heating it at 150° C. for 36 hours, and then cooling it to room temperature to obtain a heat-treated nickel-based layered double hydroxide;

[0069] (2) 1.0 mol of MH (physical method) with a particle size of 1.0 μm was uniformly dispersed in tetrahydrofuran to obtain an MH dispersion; 5.0 mol of the nickel-based layered double hydroxide after the above heat treatment was added to the MH dispersion, mechanically stirred at 300 rpm at 66° C. and refluxed for 18 h. After the reaction was completed, the mixture was repeatedly washed with deionized water for 2 to 3 times, centrifuged at 3000 rpm for 45 min, and freeze-dried at -30° C. for 36 h to obtain a nickel-based layered double hydroxide / magnesium hydroxide composite powder.

[0070] The obtained nickel-based layered double hydroxide / magnesium hydroxide composite powder is used to prepare halogen-free flame-retardant PVC. The preparation method is as follows: 55 parts of PVC (model SG-5) with a melt index of 1050g / 10min, 4 parts of nickel-based layered double hydroxide / magnesium hydroxide, 20 parts of dioctyl phthalate, 32 parts of calcium carbonate, 2 parts of barium cadmium zinc stabilizer, 1 part of polytetrafluoroethylene, and 1 part of antimony trioxide are uniformly mixed in a high-speed mixer, and then mixed by a double-roll mill at a mixing speed of 100rpm to obtain a halogen-free flame-retardant PVC composite material; wherein the temperature of the double-roll mill is set to 170°C and the mixing time is 9min.

[0071] Comparative Example 1

[0072] (1) placing a nickel-zinc layered double hydroxide in an argon gas atmosphere, heating it at 200° C. for 24 hours, and then cooling it to room temperature to obtain a heat-treated nickel-based layered double hydroxide;

[0073] (2) 1.0 mol of MH (physical method) with a particle size of 1.0 μm was uniformly dispersed in acetonitrile to obtain an MH dispersion; 0.1 mol of the above-mentioned heat-treated nickel-based layered double hydroxide was added to the above-mentioned MH dispersion, and mechanically stirred at 450 rpm and refluxed for 12 h at 82° C. After the reaction was completed, it was repeatedly washed with deionized water for 2 to 3 times, centrifuged at 5000 rpm for 20 min, and freeze-dried at -40° C. for 24 h to obtain a nickel-based layered double hydroxide / magnesium hydroxide composite powder.

[0074] The preparation method of the halogen-free flame-retardant PVC is the same as that in Example 1.

[0075] Comparative Example 2

[0076] (1) placing a nickel-copper layered double hydroxide in an argon gas atmosphere, heating it at 300° C. for 12 hours, and then cooling it to room temperature to obtain a heat-treated nickel-based layered double hydroxide;

[0077] (2) 1.0 mol of MH (physical method) with a particle size of 1.0 μm was uniformly dispersed in deionized water to obtain an MH dispersion; 12 mol of the above-mentioned nickel-based layered double hydroxide after heat treatment was added to the above-mentioned MH dispersion, and mechanically stirred at 450 rpm and refluxed for 12 h at 100° C. After the reaction was completed, it was repeatedly washed with deionized water for 2 to 3 times, centrifuged at 5000 rpm for 20 min, and freeze-dried at -40° C. for 24 h to obtain a nickel-based layered double hydroxide / magnesium hydroxide composite powder.

[0078] The preparation method of the halogen-free flame-retardant PVC is the same as that in Example 1.

[0079] Comparative Example 3

[0080] The commercially available precipitated magnesium hydroxide has a lamellar structure and has not undergone any modification treatment; the formula and preparation method of the halogen-free flame-retardant PVC are the same as those in Example 1, except that the nickel-based layered double hydroxide / magnesium hydroxide composite powder is replaced by precipitated magnesium hydroxide with a lamellar structure.

[0081] Comparative Example 4

[0082] The commercially available precipitated magnesium hydroxide does not contain a lamellar structure and has not undergone any modification treatment; the formula and preparation method of the halogen-free flame-retardant PVC are the same as those in Example 1, except that the nickel-based layered double hydroxide / magnesium hydroxide composite powder is replaced by precipitated magnesium hydroxide without a lamellar structure.

[0083] Performance Test:

[0084] The nickel-based layered double hydroxide / magnesium hydroxide composite powders prepared in Examples 1 to 4 and Comparative Examples 1 to 2 and the precipitation method MH prepared in Comparative Examples 3 to 4 were tested for particle size, specific surface area and oil absorption value. The test results are shown in Table 1:

[0085] Table 1 Test results of particle size, specific surface area and oil absorption value of Examples 1 to 4 and Comparative Examples 1 to 4

[0086]

[0087] It can be seen from the data of Examples 1 to 4 and Comparative Examples 1 to 2 in Table 1 that in Examples 1 to 4, by reasonably controlling the molar ratio of the nickel-based layered double hydroxide to MH, the particle size, specific surface area and oil absorption value of the composite particles can be effectively controlled; in contrast, when the molar ratio of the added nickel-based layered double hydroxide to MH is not appropriate, it will cause some particles to be exposed or the nickel-based layered double hydroxide will self-aggregate due to excess, thereby causing the particles to become larger, the specific surface area to decrease, and the oil absorption value to increase, which are all not conducive to the application of the composite particles in the polymer matrix. According to the data of Comparative Examples 3 to 4, it can be found that when the surface of MH is not modified, there are a large number of exposed hydroxyl groups on its surface, which are relatively polar and easy to agglomerate with each other, resulting in a significant increase in particle size, a significant decrease in specific surface area, and a significant increase in oil absorption value, which will reduce the fluidity of the polymer matrix during processing and is not conducive to the comprehensive improvement of performance. The above results show that the nickel-based layered double hydroxide / magnesium hydroxide composite powder provided by the present invention can significantly improve the powder properties of MH, which is conducive to further application.

[0088] The halogen-free flame-retardant PVC prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were molded into standard test specimens according to standard sizes, and performance tests were performed according to the standards shown in Table 2. The test results are shown in Table 3.

[0089] Table 2 Performance test standards

[0090]

[0091]

[0092] Table 3 Performance test results of PVC composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4

[0093]

[0094] It can be seen from the data of Examples 1 to 4 and Comparative Examples 1 to 2 in Table 3 that when the molar ratio of the nickel-based layered double hydroxide to MH is reasonable, the limiting oxygen index of the PVC composite material is higher, the smoke density is lower, and the corresponding tensile strength is also better. This may be mainly because the modification effect of the nickel-based layered double hydroxide / magnesium hydroxide composite particles is better, so that it can be evenly dispersed in the matrix and has better compatibility with the matrix. The appropriate coating layer can maximize the flame retardant performance and balance the mechanical properties and flame retardant properties. In contrast, when the molar ratio of the nickel-based layered double hydroxide to MH is unreasonable (the shell ratio is too low or too high) , its limiting oxygen index decreases to a certain extent, its maximum smoke density also increases to a certain extent, and its tensile strength decreases accordingly, all of which indicate that the modification effect of the composite powder is not good, resulting in a decrease in the performance of the final composite material; further according to comparative examples 3 to 4, it can be seen that by adding MH without any modification treatment, its limiting oxygen index further decreases, and the amplitude is large, the maximum smoke density also increases significantly, and the tensile strength is low, all of which indicate that MH without any modification treatment is not compatible with the matrix, has low dispersibility in the matrix, and may agglomerate, which ultimately leads to the failure of the flame retardant, smoke suppression and mechanical properties of the PVC composite material to achieve the ideal effect.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A nickel-based layered double metal hydroxide / magnesium hydroxide composite powder, characterized in that: It comprises a nickel-based layered double hydroxide shell and a magnesium hydroxide core; the molar ratio of the magnesium hydroxide core to the nickel-based layered double hydroxide shell is 1:(0.5-10); The preparation method of the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder comprises the following steps: heat-treating the nickel-based layered double metal hydroxide in an inert atmosphere and then cooling it to obtain the heat-treated nickel-based layered double metal hydroxide; mixing the heat-treated nickel-based layered double metal hydroxide with a magnesium hydroxide dispersion to perform a hybridization reaction to obtain the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder; the heat treatment temperature is 100 to 400° C., and the heat treatment time is 0.5 to 48 hours; The nickel-based layered double hydroxide is one of nickel-aluminum layered double hydroxide, nickel-cobalt layered double hydroxide, nickel-iron layered double hydroxide, nickel-manganese layered double hydroxide, nickel-gallium layered double hydroxide, nickel-rhodium layered double hydroxide, nickel-zinc layered double hydroxide, nickel-copper layered double hydroxide, nickel-lead layered double hydroxide, nickel-cadmium layered double hydroxide, nickel-chromium layered double hydroxide, nickel-calcium layered double hydroxide and nickel-vanadium layered double hydroxide; The particle size of the nickel-based double hydroxide / magnesium hydroxide composite powder is 1.0 to 2.0 μm.

2. The nickel-based layered double hydroxide / magnesium hydroxide composite powder according to claim 1, characterized in that: The particle size of the magnesium hydroxide core is 0.9-1.6 μm.

3. The method for preparing the nickel-based layered double hydroxide / magnesium hydroxide composite powder according to any one of claims 1 to 2, characterized in that: The following steps are involved: Heat-treating the nickel-based layered double metal hydroxide in an inert atmosphere and then cooling the layered double metal hydroxide to obtain a heat-treated nickel-based layered double metal hydroxide; The heat-treated nickel-based layered double metal hydroxide is mixed with a magnesium hydroxide dispersion to perform a hybridization reaction to obtain a nickel-based layered double metal hydroxide / magnesium hydroxide composite powder; The temperature of the heat treatment is 100-400° C., and the time of the heat treatment is 0.5-48 hours.

4. The preparation method according to claim 3, characterized in that: The temperature of the hybridization reaction is 60-145° C., the time is 0.5-24 hours, and the hybridization reaction is carried out under stirring conditions.

5. Use of the nickel-based layered double hydroxide / magnesium hydroxide composite powder according to any one of claims 1 to 2 or the nickel-based layered double hydroxide / magnesium hydroxide composite powder prepared by the preparation method according to any one of claims 3 to 4 as a flame retardant.

6. A halogen-free flame-retardant polyvinyl chloride composite material, characterized in that: The invention comprises the following components in parts by weight: 50-60 parts of PVC, 2-6 parts of nickel-based layered double metal hydroxide / magnesium hydroxide composite powder, and 50-60 parts of auxiliary agent; the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder is the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder according to any one of claims 1 to 2 or the nickel-based layered double metal hydroxide / magnesium hydroxide composite powder prepared by the preparation method according to any one of claims 3 to 4.

7. The halogen-free flame-retardant polyvinyl chloride composite material according to claim 6, characterized in that: The auxiliary agent includes one or more of a plasticizer, an anti-drip agent, a stabilizer, a reinforcing agent and a synergist.

Citation Information

Patent Citations

  • Preparation method of magnesium hydroxide flame retardant and the magnesium hydroxide flame retardant

    CN106554031A

  • Preparation method and application of a magnesium hydroxide-zinc borate composite flame retardant

    CN108752635B

  • Modified magnesium hydroxide flame retardant and preparation method thereof

    CN108752980A

  • Basic magnesium borate / magnesium hydroxide composite flame retardant and preparation method thereof

    CN110606982A

  • Method for preparing hexagonal flaky magnesium hydroxide for flame retardants by using large-grain-size magnesium hydroxide hydrothermal method

    CN110642274A